2013
DOI: 10.1002/pd.4279
|View full text |Cite
|
Sign up to set email alerts
|

Molecular confirmation of nine cases of Cornelia de Lange syndrome diagnosed prenatally

Abstract: We demonstrate that prenatally-detected phenotypes of CdLS, particularly severe micrognathia and bilateral upper limb defects, are associated with an increased frequency of NIPBL mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…No large studies have been performed to determine gene-based familial recurrence risks in CdLS. Infrequently, families in which non-classic CdLS segregates in an autosomal dominant manner have been reported, as has germline mosaicism leading to affected siblings born to unaffected parents 47,48 50 . Limb anomalies were seen in 66% of fetuses (likely representing a selection bias), and approximately 50% of fetuses had an abnormal facial profile (micrognathia and prominent maxilla) 51 .…”
Section: Familial Recurrence Riskmentioning
confidence: 99%
“…No large studies have been performed to determine gene-based familial recurrence risks in CdLS. Infrequently, families in which non-classic CdLS segregates in an autosomal dominant manner have been reported, as has germline mosaicism leading to affected siblings born to unaffected parents 47,48 50 . Limb anomalies were seen in 66% of fetuses (likely representing a selection bias), and approximately 50% of fetuses had an abnormal facial profile (micrognathia and prominent maxilla) 51 .…”
Section: Familial Recurrence Riskmentioning
confidence: 99%
“…To date 333 different heterozygous NIPBL mutations have been identified in 391 CdLS patients, 28 of whom belong to 13 families (43-45); 278 of these mutations were compiled in an excellent recent review and subsequently 55 further novel mutations have been identified (43)(44)(45)(46)(47)(48).…”
Section: The Genetic Basis Of Cdlsmentioning
confidence: 99%
“…Chromosomal abnormalities, cardiac malformations, and many genetic syndromes have been associated with an increased thickness of NT. Previous studies reported an abnormal thickness of NT in the first trimester (Dempsey et al, ) at 11 (Sekimoto et al, ; Huang and Porto, ) and 12 (Bruner and Hsia, ) weeks of gestation, in cases with a normal karyotype and postnatally diagnosed as affected by CdLS. On the other hand, affected cases with normal first trimester NT have also been reported (Chong et al, ; Kanellopoulos et al, ; Sepulveda et al, ; Weichert, ; Clark et al, ; Spaggiari et al, ; Dempsey et al, ), suggesting that NT values may not be considered a specific early marker of CdLS.…”
Section: Nuchal Translucencymentioning
confidence: 91%